Komunikasi Terapeutik Dalam Mengurangi Kecemasaan Korban Akibat Pelechan Seksual - Rara Porlinta; Suryati Suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: Acts of sexual harassment increase every year. Not only in big cities but in rural areas far from the hustle and bustle of the city. Various methods are used to overcome sexual harassment, including for victims who experience sexual harassment so that they can recover. Sexual harassment has a tremendous impact on victims who experience mental shocks. It cannot be denied that sexual harassment will have an anxious impact on victims. This shows that there are very serious consequences resulting from both physical and verbal sexual harassment. It requires special treatment that can recover, which is not only done medically, especially treatment that is carried out communicatively (therapeutic communication). The research aims to determine the extent to which therapeutic communication can overcome victims' anxiety due to sexual harassment. By using qualitative research methods, this research produced several important notes on therapeutic communication carried out by researchers. Researchers carry out therapeutic communication with clients in stages, and each stage has different but continuous actions. The results of this study reveal that therapeutic communication as an effort to cure victims' anxiety due to sexual harassment is a psychological approach carried out in four stages, namely the pre-interaction stage, orientation stage, work stage and termination stage. As a form of concrete and in-depth effort and providing the latest views on victims of sexual harassment.